Pengaruh Profitabilitas Dan Leverage Terhadap Penghindaran Pajak - Putri Gantine Lestari (LPPM UNIBI, 2020)
The purpose of this study was to examine the effect of profitability and leverage on tax avoidance. The population of this study are mining companies listed on the Indonesia Stock Exchange in 2017-2019. The research sample was defined as 45 samples and the data analysis technique used multiple linear regression. Based on the results of the research, profitability partially has no effect on tax avoidance, leverage has a positive effect on tax avoidance and simultaneously profitability and leverage have an effect on tax avoidance.